2022
DOI: 10.1007/s10072-022-06424-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic recommendations in adult dystonia: a joint document by the Italian Society of Neurology, the Italian Academy for the Study of Parkinson’s Disease and Movement Disorders, and the Italian Network on Botulinum Toxin

Abstract: The diagnostic framework and the therapeutic management of patients with adult dystonia can represent a challenge for clinical neurologists. The objective of the present paper is to delineate diagnostic and therapeutic recommendations for dystonia provided by a panel of Italian experts afferent to the Italian Society of Neurology, the Italian Academy for the Study of Parkinson's Disease and Movement Disorders, and the Italian Network on Botulinum Toxin. We first discuss the clinical approach and the instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…In clinical practice, foot dystonia is often encountered early in the morning. Botulinum toxin injections are often the first line therapy for several forms of dystonia [ 66 ]. Our review has shown one blinded and at least two prospective studies reporting significant improvement of foot dystonia in PD following injection of BoNT into toe flexors.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, foot dystonia is often encountered early in the morning. Botulinum toxin injections are often the first line therapy for several forms of dystonia [ 66 ]. Our review has shown one blinded and at least two prospective studies reporting significant improvement of foot dystonia in PD following injection of BoNT into toe flexors.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for both case and control subjects were age 18 or older, any sex, and the willingness and mental/physical ability to sign informed consent and participate in the protocol. Case patients were enrolled if they had a diagnosis of focal idiopathic CD made by an experienced movement disorder neurologist [ 25 , 26 ]. Exclusion criteria were secondary CD and co-existing medical conditions/surgical interventions that could confound assessment of CD.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-seven native Chinese-speaking WD patients with extremities dystonia and thirty-seven age-and sex-matched HCs were recruited from the First Affiliated Hospital of Anhui University of Traditional Chinese Medicine (AUTCM) between April 2021 and April 2022. Patient inclusion criteria were as follows: met the diagnostic guidelines for WD established by the European Association for Liver Research in 2012 [16]; 12-40 years old; normal communication, audio-visual reading and writing abilities; or diagnosed with multisegmental dystonia, mainly manifested in the extremities, by the relevant dystonic standard [17][18][19]. The exclusion criteria were as follows: obvious head shaking, which affects the magnetic resonance data acquisition; a history of craniocerebral surgery or metal implants in the body; the use of drugs that can affect muscle tension, such as baclofen and benzhexol, in the 2 months before the study; the disease in rapid progress; or other diseases that affect muscle tension and stiffness, such as brain injury, myositis, etc.…”
Section: Participantsmentioning
confidence: 99%